Círio of Igarapé Grande: riverine identity exercise - Saldanha, Inácio dos Santos (2021)
This essay proposes a connection between present and past through an Ethnography fulfilled in Igarapé Grande riverine community, in 2017 and 2018.  Igarapé Grande is sited by the Bravo igarapé, in João Pilatos island, Ananindeua, metropolitan region of Belém (Pará). This island, like its neighbors, is little known by near continental inhabitants, in despite of the richness of its Histories and customs. Amidst the customs, one reveals the uses and the significations of the island and community spaces: the Círio of Nossa Senhora da Conceição, a pilgrimage created back in 1986 by Raimundo Nonato Ferreira Pantoja.  The event crosses the island forest on a trail at the second Sunday of December. That's the photographs of Raimundo Pantoja the starting point to the essay, as personal records of the editions back in 1980s and 1990s. His records expose the intention to explore the basic references of the islander through their religiosity. So, the river, the wharf, the trail and the family memories become the the script of the pilgrimage. Soon, we reencounter the Círio of Igarapé Grande in 2017 through the Ethnographic view. We rich the community port, face the Nossa Senhora da Conceição Capel and the first landscapes in the way to the trail traveled by the devotees. Again, the spaces are explored to reveal the inhabitants cosmovision.